Workplace Support for Mental Health Workers Who Are Parents: A Feasibility Study - Dunn, Abby; Dixon, Clare; Thomson, Abi; Cartwright-Hatton, Samantha (Frontiers in Psychology, 2022)
Background Mental health workers are subject to high levels of occupational stress which is associated with poorer health and wellbeing and impaired patient outcomes. For individuals operating in high stress environments, reducing challenge at home, in particular around parenting, has been found to generalise into improvements in the professional domain. The present study sought to investigate the effectiveness and feasibility of brief targeted workplace intervention to support workers in terms of their parental role. Design/methodology An uncontrolled evaluation of a series of three-session parenting-focused workshops delivered to employees of a large Mental Health Trust. A pre-post-follow-up design was used to investigate effects on outcomes including parenting practice and experience, wellbeing, stress, and occupational self-efficacy. Intervention feasibility and acceptably was also evaluated. Findings Data from 15 participants who completed measures pre-post indicates the workshops were associated with improved parenting practice and experience at a p<.005 level. Improvements were reported at 6-month follow up. Participant satisfaction and course acceptability was highly rated by 100% of participants.